MICROPLÁSTICOS EM ÁGUA CINZA - GABRIELA DE FÁTIMA XAVIER DIAS (2024)
Microplastics have received increasing attention in recent years due to their wide distribution in the environment. The chemical composition of microplastics, as well as the pollutants adsorbed on them, can have negative impacts on aquatic organisms and consequently affect human life. Washing clothes made from synthetic materials has been identified as an important source of microscopic fibers. Considering that the fraction of gray water produced in the laundry area represents around 30% of all the wastewater generated in a household and that this fraction is a promising alternative source of urban water, the aim of this work was to evaluate the influence of mechanical and chemical processes and fabric wear on the release of microplastics into gray water during the laundry process. Eight washes of synthetic bed linen were carried out using washing powder and fabric softener. From the laundry washes, a 61% drop in microplastics was observed in the mechanical washes and a 12% drop in microplastics in the mechanical + chemical washes present in the gray water, and that washing using chemical products preserved the clothing fibers. Based on the results, the generation of 1,20x104 microplastics/LAC.kg of synthetic clothing was estimated and based on data from the literature, considering the generation of 28,1 L/in hab.day of gray water from the washing machine, a person wearing synthetic clothing three times a week generates 6,88 x 108 microplastics in a year. Keywords: Domestic sewage, laundry, reuse, source separation, microfibers